If it's not what You are looking for type in the equation solver your own equation and let us solve it.
3(4x+2)=2(6x+5
We move all terms to the left:
3(4x+2)-(2(6x+5)=0
We multiply parentheses
12x-(2(6x+5)+6=0
| 6x-4=-4x+1 | | 5=-1.5+2.5x | | 7+(-3x^2)x=0. | | 4x-4-3x+3=2x-8 | | h=13/9=5 | | 7x-5(x-6)=-18 | | 6x-21=2x+35 | | g/4+11=14 | | 6=-1.5+2.5x | | -2(x+0.25)+1=5 | | 5x-20=12x-9x | | 3x+7=-5(x-3)x= | | x-2+x-5=11 | | m-6-15m=50 | | K^2+4r+4=0 | | 2w+2(2w+5)=24 | | 6=2+2k | | 6•2g-1=13g | | 9=-1.5+2.5x | | 1=3u-2 | | -2(x+1/4)+1=5 | | x/7x+15=38 | | 2x/5000=346 | | 20(11+3n)=12n | | 5a+9=8a | | 2(-3m-7)=4 | | 2^3^x=5 | | 2w+29(2w+5)=24 | | 8x-21=2x+31 | | 11+5m=6m+6 | | -2x+3-5x=-29 | | x(12x+6)=0 |